Meteoritic evidence of a late superflare as source of 7Be in the early solar system - Mishra, Ritesh Kumar; Marhas, Kuljeet Kaur (Nature astronomy, 2019)
Li and Be isotopic measurements of calcium-aluminium inclusions (CAIs) in the Efremovka meteorite suggest that the solid and gaseous precursors of CAIs were irradiated by a superflare during the last stages of the pre-main-sequence evolution of the Sun.
Im Titel ist "7" vor "BE" hochgestellt
Gesehen am 29.01.2020